Linguistic, Aesthetic And Cultural Aspects Of Translating Literary Texts (Arabic-English): A Model For Translation Pedagogy - Elewa, Abdelhamid (Ijaz Arabi Journal of Arabic Learning, 2024)
The main aim of this paper is to explore the different linguistic, aesthetic, and cultural aspects of literary translation. The paper examines the various features of literary translation at both macro and micro levels. It focuses on those features of literary texts that are characteristic of literary works. First, we follow the standard linguistic paradigm in the discussion of literary translation, including phonology, morphology, syntax, semantics, and the aesthetic and cultural features of literary texts. The qualitative method is used to explore the various features of literary translation to identify the recurring linguistic and literary devices lacking systematic forms and patterns to find a comparable genre-specific form in the target language. The model proposed consists of five stages: (1) Retention of sound devices, (2) Retention of syntactic patterns, (3) Retention of semantic features, (4) Retention of figurative language, and (5) Retention of the cultural aspects. The model is a descriptive model for analyzing literary translation procedures and can be used as a pedagogical model for translation practice. Findings show that employing this model would offer translation students new insights to describe challenging linguistic, aesthetic, and cultural features in the source texts to think of some practical solutions for translating literary works.